Islam Sebagai “Post-Kristen”; Deskripsi Perjumpaaan Teologis Islam-Kristen - Samsi Pomalingo; Arfan Nusi (LPPM IAIN Sultan Amai Gorontalo, 2020)
This article uses an esoteric approach in explaining the intersection of religions in the Yudaeo tradition. There is a misunderstanding of religion because it is seen from an exoteric approach. As a result, people tend to judge that this religion is right and another is wrong. Whereas Abraham is known as the father of monotheistic religions, namely Judaism, Christianity and Islam. The vision of the Judaeo-Christian-Islamic tradition is an indicator of the three religions as monotheistic religions whose teachings are inseparable and cannot be polarized between one another. However, for certain circles, Islam and Christianity are not seen as Yudaeo traditions, because they see the root of the problem that often causes conflicts between Islam and Christianity, especially in the position or capacity of the Koran as Muhaimin. The conflicts that often occur between the two religions often cause discomfort in theological encounters. This resulted in the relationship between the two religions experiencing unfounded